The Experience of a Gluten-free Diet in Children with Type 1 Diabetes and Celiac Disease. Issue 1 (18th June 2021) - Kakkar, Rohan; Fung, Alex; Barker, Collin; Foster, Alice; Hursh, Brenden E
Abstract: Objective: This study examined overall self-reported adherence to gluten-free diet (GFD) in children with type 1 diabetes and celiac disease (T1DCD) compared to children with celiac disease (CD). Secondary objectives included gaining insight into self-reported symptoms, barriers to adherence, and experience of a GFD between groups. Methods: Children <18 years old who had been seen at BC Children's Hospital for T1DCD or CD were invited to participate in a web-based questionnaire and medical record review. Results: A total of 26 children with T1DCD and 46 children with CD participated in the study. The groups' demographics and symptoms of CD were similar; however, a greater proportion of those with T1DCD were asymptomatic at diagnosis (T1DCD 27%; CD 7%; P = 0.016). Overall adherence to a GFD was high in both groups (T1DCD 92%; CD 100%; P = 0.38) but those with T1DCD reported a significantly less positive effect on their health ( P = 0.006) and a significantly greater negative effect on activities from a GFD ( P = 0.03). Children with T1DCD reported more significant barriers to eating gluten-free at home and at restaurants, specifically with social pressure, cost and taste compared to those with CD only. Conclusion: Children with T1DCD face specific barriers in adherence that are more impactful compared with children living with CD. These children are more often asymptomatic at diagnosis, and they go on to experience different impacts of a GFD spanning across home and social settings. Given the complexity of having a dual diagnosis, CD care should be tailored specifically to children living with T1DCD.